A cold and organic solvent tolerant lipase produced by Antarctic strain Rhodotorula sp. Y‐23. (14th February 2018) - Maharana, Abhas K.; Singh, Shiv M.
Abstract : Psychrotolerant yeast Rhodotorula sp. Y‐23 was isolated from the sediment core sub‐samples of Nella Lake, East Antarctica. Isolate was screened for lipase production using plate assay method followed by submerged fermentation. Production optimization revealed the maximum lipase production by using palmolein oil (5% v/v), pH 8.0 and inoculum size of 2.5% v/v at 15 °C. The potential inducers for lipase were 1% w/v of galactose and KNO3, and MnCl2 (0.1% w/v). Final productions with optimized conditions gave 5.47‐fold increase in lipase production. Dialyzed product gave a purification fold of 5.63 with specific activity of 26.83 U mg −1 and 15.67% yields. This lipase was more stable at pH 5.0 and −20 °C whereas more activity was found at pH 8.0 and 35 °C. Stability was more in 50 mM Fe 3+, EDTA‐Na (20 mM), sodium deoxycholate (20 mM), H2 O2 (1% v/v), and almost all organic solvents (50% v/v). Tolerance capacity at wider range of pH and temperature with having lower K m value i.e., 0.08 mg ml −1 and higher V max 385.68 U mg −1 at 15 °C make the studied lipase useful for industrial applications. Besides this, the lipase was compatible with commercially available detergents, and its addition to them increases lipid degradation performances making it a potential candidate in detergent formulation.